A table full of love : recipes to comfort, seduce, celebrate & everything else in between - McAlpine, Skye (Bloomsbury Publishing, 2023)
"For Skye McAlpine, there's no better way to say "I love you" than with food. With recipes collected over a lifetime of meals prepared and shared, and with sections like Comfort, Seduce, Spoil, Nourish, and Cocoon, A Table Full of Love teaches you the culinary love language to say it, too"--